2009
DOI: 10.1038/eye.2009.248
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmological screening of a paediatric cochlear implant population: a retrospective analysis and 12-year follow-up

Abstract: Aims To determine the nature and prevalence of ophthalmological findings for a cohort of children in a paediatric cochlear implant program and to assist the clinician in devising an investigative plan for this population. Methods Retrospective medical record review of children who underwent multichannel cochlear implantation at a tertiary care hospital between February 1996 and July 2008. Results In all, 141 children (mean age 28 months, range 16 months to 9 years) had complete medical record documentation con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 27 publications
(15 reference statements)
4
8
1
3
Order By: Relevance
“…This difference may well be explained by our inclusion criterion of bilateral vestibular impairment and systematically requesting an ERG for those cases. Similarly, we detected a higher prevalence of refractive errors (75%) than previous reports, which was generally been estimated to be around 40-50% (28,29). This can reflect the differences in the definitions of myopia and hyperopia used as inclusion criteria.…”
Section: General Clinical Observationssupporting
confidence: 77%
See 1 more Smart Citation
“…This difference may well be explained by our inclusion criterion of bilateral vestibular impairment and systematically requesting an ERG for those cases. Similarly, we detected a higher prevalence of refractive errors (75%) than previous reports, which was generally been estimated to be around 40-50% (28,29). This can reflect the differences in the definitions of myopia and hyperopia used as inclusion criteria.…”
Section: General Clinical Observationssupporting
confidence: 77%
“…An abnormal ERG had a significant correlation (p < 0.0001) with the genetic diagnosis of USH1 as seen in our 14 patients (Table 3). In USH1, the ERG is abnormal early, before the retinal appearance (14,19,28,32) and the responses deteriorate slowly. If the ERG is normal by the age of 6-7 years, it most probably will stay normal and can be relied on to exclude USH (14).…”
Section: The Role Of Ergmentioning
confidence: 99%
“…This study showed a slightly higher incidence (50%) of ocular pathologies in congenitally deaf patients. In the same manner, refractive disorders were the leading pathology, with a higher incidence of 44.9% (35 cases), compared to the 16%-42.7% found across previously published studies (4,7,(9)(10)(11)(16)(17)(18)(19)(20). Since our study group was composed of adult individuals, it was easy to detect even a small degree of refractive problems like myopia, which may increase during the adolescent years.…”
Section: Discussionsupporting
confidence: 57%
“…Moreover, less myopic cases were found in this group. Previous studies such as Hanioglu-Kargi, 4 Mafong, 14 Siatkowski, 15 and Falzon, 16 indicated that hyperopia is the most common refractive error in deaf students. Nevertheless, there are some studies that did not show remarkable differences between prevalence of hyperopia and myopia, and even a few studies like those of Sharma, 17 Leguire, 10 and Al-ani 9 indicated that myopia was more common.…”
Section: Discussionmentioning
confidence: 96%
“…Although most of the studies support our finding that hyperopia is the most common refractive error, their findings are not quite valid because they lack a control group. 4 , 14 , 15 , 16 …”
Section: Discussionmentioning
confidence: 99%